2022
DOI: 10.1674/0003-0031-188.1.74
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Prairie Management Practices for Maintaining Habitat Quality for the Endangered Poweshiek Skipperling Butterfly in Canada

Abstract: The Poweshiek skipperling (Oarisma poweshiek) was once a common prairie butterfly in central North America, but is now critically endangered in Canada and the United States. The Poweshiek skipperling is confined to the largest remaining tall grass prairie in Canada, which is currently managed using grazing and fire to maintain prairie habitat and prevent forest and shrub encroachment. To support re-introduction, restocking, and recovery of this critically endangered species, it is necessary to understand the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 81 publications
(118 reference statements)
2
9
1
Order By: Relevance
“…Sites in Manitoba that had been intentionally burned approximately three to six years earlier supported relatively higher abundances of Poweshiek skipperlings than did sites with more recent and older burns and sites where grazing took place (Dupont-Morozoff et al 2022). Disturbances such as a cutting actionhayingand prescribed burns may improve the suitability of habitats for butterflies (Swengel 1996;Thom and Daniels 2017) but ought to be compatible with the life history of these same butterflies to reduce mortality (Swengel andSwengel 1999, 2015).…”
Section: Broader Conclusionmentioning
confidence: 99%
“…Sites in Manitoba that had been intentionally burned approximately three to six years earlier supported relatively higher abundances of Poweshiek skipperlings than did sites with more recent and older burns and sites where grazing took place (Dupont-Morozoff et al 2022). Disturbances such as a cutting actionhayingand prescribed burns may improve the suitability of habitats for butterflies (Swengel 1996;Thom and Daniels 2017) but ought to be compatible with the life history of these same butterflies to reduce mortality (Swengel andSwengel 1999, 2015).…”
Section: Broader Conclusionmentioning
confidence: 99%
“…Gray), and little bluestem (Schizachyrium scoparium (Michs.) Nash) (Dupont Morozoff 2013;Henault and Westwood 2022). Larvae feed on host plants throughout the remainder of the summer and enter a form of dormancy as larvae in mid-to-late September (K. Eckhardt (personal communication, 24 October 2023)), overwintering at the base of host plant species in or above the litter layer (Borkin 1995;Selby 2005;Henault and Westwood 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Gray) B. Boivin) have been the primary nectar plants of adults in Manitoba (Catling and Lafontaine 1986;Semmler 2010;Dupont Morozoff 2013;Westwood et al 2020), though Poweshiek skipperling have recently been observed nectaring on other species (Henault 2021). Catling and Lafontaine (1986) observed the highest Poweshiek skipperling densities in areas with high pale-spiked lobelia densities, but pale-spiked lobelia was not present during Semmler (2010) and Dupont Morozoff's (2013) studies and was also scarce in Henault's (2021) study. In Michigan, Poweshiek skipperling are more likely to be found in areas with high numbers of their preferred nectar plants (Belitz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations